Dinamika Hukum Pernikahan di Indonesia: Perbedaan Aliran Keagamaan Menjadi Sebab Perceraian - Miftah Elfaruq (Indonesian Journal of Humanities and Social Sciences, 2023)
Divorce due to differences in religious denominations is a prevalent issue within the Indonesian judicial system. Despite laws such as Government Regulation No. 9 of 1975 on the Implementation of Law No. 1 of 1974 concerning Marriage and Article 116 of the Compilation of Islamic Law (KHI) not explicitly mentioning that religious denominational differences are a cause of divorce, cases of this nature frequently emerge in the courts. This research aims to uncover how judges in Religious Courts understand and interpret the reasons for divorce related to differences in religious denominations and the extent to which their decisions align with the principles of Islamic law. The research employs a normative juridical approach by analyzing legal provisions related to divorce and reviewing several judicial decisions on divorce cases stemming from religious denominational differences. The findings of this research indicate that judges often interpret divorce cases related to religious denominational differences as triggers for conflicts that are difficult to mend. This interpretation is in line with the applicable legal provisions. However, this approach sometimes disregards the underlying objectives of family formation (maqÄshid al-usrah).